Conditions of access to an antenatal care program in a primary health care center at Pasto City, Colombia - Tutal Muñoz, Luis Miguel (2019)
Introduction: Prenatal care is the main tool for prevention of complications of pregnancy, childbirth and the puerperium. Nevertheless, rates of deaths and diseases related to gestation remain unacceptably high, especially in developing countries. Objective: To describe the conditions of access to prenatal care in a primary care center in the city of Pasto, Nariño, Colombia. Methods: We conducted a descriptive, cross-sectional study. We interviewed twenty-four women with gestational age between 36 and 40 weeks, attending prenatal care at the Pandiaco Health Center, level I of care in Pasto City, Colombia, during the year 2015. The data obtained were analyzed with the statistical software SPSS 16.0 for Windows. Results: Approximately 50% of pregnant women had less than four prenatal care visits during pregnancy. Labor, home, children care, and economic burden were referred as the main barriers to regular attendance. Conclusions: Home and children care, and the need to work, represented the main barriers to prenatal care access among the population studied.